Walking to Africa. - Le Bas, Jessica (Auckland University Press, 2009)
Portraying a parent's experience of coming to terms with the new and frightening world of mental health care, this narrative explores the myriad foreign ways of diagnosis and treatment. Written from a mother's perspective, the poetic sequence displays the anguish and complexity of dealing with mental illness, describing the events of an ordinary family?the numerous visits to doctors, the treatments that don't work, and the people who suddenly have answers and heartbreaking histories of their own to tell. At the heart of the book lies an outstanding set of poems about electroconv.